Pengembangan LKPD Elektronik Berbasis Konstruksivisme pada Tema Indahnya Kebersamaan Siswa Kelas IV SDN 01 Sukabumi - Prasojo, Agus Dwi (Lembaga Yasin AlSys, 2021)
To realize interesting learning, it is necessary to develop learning media, one of the interesting learning media is Electronic LKPD. The developed Electronic LKPD is by depicting examples that are preferred by students, so that the learning media developed is based on constructivism as generative learning, namely creating something meaning from what is learned. This study aims to determine the feasibility of the constructionism-based Electronic LKPD learning media through the results of expert validation and to determine student responses to the developed learning media. The research method used in this research is using the ADDIE model. The research subjects involved consisted of experts (material experts and media experts) and fourth grade students at SDN Sukabumi. Experts provide an assessment of the level of material validity and suitability of the Electronic LKPD design, while educators and students assess the level of attractiveness of the Electronic LKPD developed by researchers. The results obtained are the feasibility of the Electronic LKPD. Based on the expert's assessment, it is categorized as very feasible, with a validation percentage of 86% material experts and 94% media experts. Educators and students gave a positive response to the attractiveness of Electronic LKPD as a learning medium, with the percentage of educators responding 89%, small group testing 86%, and 85% field testing categorized as very interesting. The development of constructivism-based electronic LKPD is very feasible and gets a positive response to be used as a learning medium.